Geospatial Analysis with SQL : A hands-on guide to performing geospatial analysis by unlocking the syntax of spatial SQL /: A hands-on guide to performing geospatial analysis by unlocking the syntax of spatial SQL. (2023) - Bonny P McClain
No abstract available